Chemical composition and antifungal activity of Mentha spicata L. plant from Sulaimaniyah in Iraq - Mohammed, Lana MA.; M. Salah, Tara Faeq; Qader, Karzan O. (Kurdistan Journal of Applied Research, 2017)
Aerial parts of Mentha plants were collected from Sulaimaniyah city, during 15th Mar to 1st July 2016. Clevenger apparatus was used for plant sample distillation and then obtained essential oils were analyzed by GC and GC/MS. The GC–MS analysis resulted in the detection of thirty-eight compounds which made up 100% of the total plant essential oil. The major components of the oil were (54.44%) of 2-Cyclohexen-1-one, 2-methyl-5-(1- methylethenyl)-, (R)-, (27.72%) of D-Limonene, (3.29%) of 2-Cyclohexen-1-ol, 2-methyl-5-(1- methylethenyl)-, trans-, (2.16%) of Cyclohexanol, 2- methyl-5-(1-methylethenyl)-, (1.83%) of Bicyclo[3.1.0] hexan-2-ol,2-methyl-5-(1-methylethyl)- (1.alpha.,2.beta.,5.alpha.) and (1.03%) of 3- Cyclohexen-1-ol, 4-methyl-1-(1-methylethyl)-, (R)-. The significant inhibition percentages of Mentha spicata plants extract on the Aspergillus niger mycelial growth were 16.78%, 18.92%, 23.21%, 28.57% and 36.78%, in 32%, 34%, 36%, 38% and 40% dilution respectively, while other concentrations showed no significant effect.